2002
DOI: 10.1086/344603
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of [O [CSC]i[/CSC]] λ6300/Hα Line Intensity Ratios for Four O Star H [CSC]ii[/CSC] Regions

Abstract: We have used the Wisconsin H Mapper facility to measure the [O i] 6300/H line intensity ratios for four O star H ii regions: S27 (observation coordinates l = 6=3, b = +23=6), S252 (l = 190=1, b = +0=6), S261 (l = 194=1, b = À1=9), and S264 (l = 195=1, b = À12=0). We find that the ratios range from 0.0015 to 0.0053. These results are roughly a factor of 10 lower than measured [O i]/H ratios in directions that sample the warm ionized component of the interstellar medium. This difference implies a significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…The spectroscopic or photometric distances to the star within S261 are 1.4 kpc (Georgelin & Georgelin 1976) and 1.5 kpc (Garmany et al 1982), which are close to that of S255. The radial velocity of the Hα line emission of S261, v LSR = +5.6 km s ¡1 (Hausen et al 2002) is close to the lower limit of those of S254 -S258, v LSR = +6.0 -+11.1 km s ¡1 , measured in CO and Hα lines. On the other hand, S259, which overlaps with G192, seems separated from the rest of the Hii regions in the field.…”
Section: Distance To G1928¡11supporting
confidence: 74%
See 1 more Smart Citation
“…The spectroscopic or photometric distances to the star within S261 are 1.4 kpc (Georgelin & Georgelin 1976) and 1.5 kpc (Garmany et al 1982), which are close to that of S255. The radial velocity of the Hα line emission of S261, v LSR = +5.6 km s ¡1 (Hausen et al 2002) is close to the lower limit of those of S254 -S258, v LSR = +6.0 -+11.1 km s ¡1 , measured in CO and Hα lines. On the other hand, S259, which overlaps with G192, seems separated from the rest of the Hii regions in the field.…”
Section: Distance To G1928¡11supporting
confidence: 74%
“…The expected count rate per EM is 8 ¢ 10 ¡4 counts s ¡1 arcmin ¡2 at T 5 ¢ 10 6 K in band 5 (0.56 -1.21 keV), for example, when a maximum extinction of N H 10 22 cm ¡2 is assumed (see Figure 7 of Snowden et al 1997). The count rate of G192, for an EM = 190 cm ¡6 pc, would be 0.16 counts s ¡1 arcmin ¡2 , while, the rms of the G192 a Optical size (Sharpless 1959) b Hα emission line radial velocity (Fich et al 1990), except S261, which is from Hausen et al (2002). c CO radial velocity (Blitz et al 1982).…”
Section: G192 As An Evolved Thermal-composite Snr Interacting With Nementioning
confidence: 99%
“…Nevertheless, high-sensitivity, high-resolution spectroscopic measurements with WHAM have managed to resolve the Galactic emission from atmospheric emission to provide reliable measurements in a few select directions. These observations indicate that H + /H > 90% for T > 8000 K (Hausen et al, 2002;Reynolds et al, 1998).…”
Section: B Ionization Statementioning
confidence: 69%
“…The similar first ionization potentials of N and H (14.5 and 13.6 eV, respectively), along with N-H charge exchange, mean that in the WIM the ionization fraction of N + /N is expected to be similar to H + /H. The fraction H + /H is observed to be near unity in the WIM Hausen et al 2002a), and the high second ionization potential of N (29.6 eV ) means that little N is likely to be in the form of N ++ . This is supported by the weak [O iii]/ H ratios in the WIM (see below) and by photoionization modeling (e.g., Sembach et al 2000), which have shown that N þ /N % 0:8 over a wide range of input spectra and ionization parameters.…”
Section: Emission-line Ratios and Physical Conditionsmentioning
confidence: 90%